Determining the Antimicrobial Susceptibility Pattern of Bacterial Isolates from Wound Infection and Their Sensitivity to Antibiotic Agents: A Retrospective Study - Hrishikesh Sawdekar; Radha Sawdekar; Vinod R. Wasnik (Advanced Concepts in Medicine and Medical Research Vol. 5, 2023)
This chapter aims to determine antimicrobial susceptibility pattern of bacterial isolates from wound infection and their sensitivity to antimicrobial agents. Surgical wound infection is clinically defined as purulent discharge from the surgical wound. This retrospective study was carried out among patients with wound infection in Suyash super speciality hospital, during January, 2012 and December, 2013. Sterile cotton swabs were used to capture the wound swab, which was then processed for bacterial isolation and systemic antimicrobial agent susceptibility testing.A total of 258 specimens yielded 78 bacterial isolates in this investigation, representing a 31.2% isolation rate. Gram positive staphylococci 36 (46.2%) and gram negative streptococci 18 (23.1%), gram negative pseudomonas 12 (15.4%), and gram negative proteus 8 (10.4%) were the most common bacteria isolated from wounds. Ten (12.8%) and 68 (87.2%) of the bacterial isolates were gram negative and gram positive bacteria, respectively. In the current investigation, the majority of pathogens identified from wound isolates exhibited a significant prevalence of resistance to the most often prescribed, more recent antibiotics used to treat bacterial infections. Consequently, it is important to take antibiotics properly.